Red Blood Cell Distribution Width and the Platelet Count in Iron-deficient Children Aged 0.5–3 Years. (17th November 2015) - Akkermans, M.D.; Uijterschout, L.; Vloemans, J.; Teunisse, P.P.; Hudig, F.; Bubbers, S.; Verbruggen, S.; Veldhorst, M.; de Leeuw, T.G.; van Goudoever, J.B.; Brus, F.
Abstract : Early detection of iron deficiency (ID) and iron deficiency anemia (IDA) in young children is important to prevent impaired neurodevelopment. Unfortunately, many biomarkers of ID are influenced by infection, thus limiting their usefulness. The aim of this study was to investigate the value of red blood cell distribution width (RDW) and the platelet count for detecting ID(A) among otherwise healthy children. A multicenter prospective observational study was conducted in the Netherlands to investigate the prevalence of ID(A) in 400 healthy children aged 0.5–3 years. ID was defined as serum ferritin (SF) <12 μg/L in the absence of infection (C-reactive protein [CRP] <5 mg/L) and IDA as hemoglobin <110 g/L combined with ID. RDW (%) and the platelet count were determined in the complete blood cell count. RDW was inversely correlated with SF and not associated with CRP. Calculated cutoff values for RDW to detect ID and IDA gave a relatively low sensitivity (53.1% and 57.1%, respectively) and specificity (64.7% and 69.9%, respectively). Anemic children with a RDW >14.3% had a 2.7 higher odds (95% confidence interval [CI]: 1.2–6.3) to be iron deficient, compared with anemic children with a RDW <14.3%. The platelet count showed a large range in both ID and non-ID children. In conclusion, RDW can be helpful for identifying ID as the cause of anemia in 0.5- to 3-year-old children, but not as primary biomarker of ID(A). RDW values are not influenced by the presence of infection. There appears to be no role for the platelet count in diagnosing ID(A) in this group of children.